Analysis of P ® film-coated caplet quality control by implementing statistical process control method at PT. YF - Oktavia Eka Puspita; Achmad Fudholi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Manufacturing of film-coated caplet dosage form is a multi-steps process, including weighing, blending, granulating, drying, compression, coating, and packaging. Every manufacturing process is influenced by natural variation and assignable variation which caused the process operates out-of control and interfering consistency and attainment of output quality specification. Based on the above background a research was conducted upon manufacturing process of P® film coated caplet at PT.YF. This research was limited for core caplet compression step and film coating step instead of entire production process. The purposes of this research were analyzing core caplet compression process and coating process and measuring process capabilityof those steps in meeting the pre-determined quality specifications. Investigation of 20 latest consecutive batch record documents within 2009 period was conducted in collecting quantitative data measurement of caplet quality characteristics including weight uniformity, hardness, friability, disintegration,and dissolution of drug substance of P® film coated caplet. Those data were analyzed using control chart SPC method and process capabilitywas measured by Cpk index. The results showed that from caplet core compression step the control chart of caplet weight uniformity and friability indicates statistically in-control, meanwhile step the control chart of hardness; disintegration time and dissolution of Paracetamol ; Ibuprophen indicates statistically out-of control. The result of film coating step of P® film-coated caplet showed that the control chart of weight uniformity; hardness and Ibuprophen dissolution indicates statistically out-of control, meanwhile disintegration time and Paracetamol dissolution was statistically in control. The process capability index, Cpk. of core caplet weight uniformity: 1.375, and Paracetamol P® film-coated caplet dissolution: 1,841,Key words : Natural variation, assignable variation, Statistical Process Control, P® filmcoated caplet